Synthesis and Characterization of Novel 2-Acyl-3-trifluoromethylquinoxaline 1,4-Dioxides as Potential Antimicrobial Agents - Galina I. Buravchenko; Dmitry A. Maslov; Md Shah Alam; Natalia E. Grammatikova; Svetlana G. Frolova; Aleksey A. Vatlin; Xirong Tian; Ivan V. Ivanov; Olga B. Bekker; Maxim A. Kryakvin; Olga A. Dontsova; Valery N. Danilenko; et al. (MDPI AG, 2022)
The emergence of drug resistance in pathogens leads to a loss of effectiveness of antimicrobials and complicates the treatment of bacterial infections. Quinoxaline 1,4-dioxides represent a prospective scaffold for search of new compounds with improved chemotherapeutic characteristics. Novel 2-acyl-3-trifluoromethylquinoxaline 1,4-dioxides with alteration of substituents at position 2 and 6 were synthesized via nucleophilic substitution with piperazine moiety and evaluated against a broad panel of bacteria and fungi by measuring their minimal inhibitory concentrations. Their mode of action was assessed by whole-genomic sequencing of spontaneous drug-resistant Mycobacterium smegmatis mutants, followed by comparative genomic analysis, and on an original pDualrep2 system. Most of the 2-acyl-3-trifluoromethylquinoxaline 1,4-dioxides showed high antibacterial properties against Gram-positive strains, including mycobacteria, and the introduction of a halogen atom in the position 6 of the quinoxaline ring further increased their activity, with 13c being the most active compound. The mode of action studies confirmed the DNA-damaging nature of the obtained quinoxaline 1,4-dioxides, while drug-resistance may be provided by mutations in redox homeostasis genes, encoding enzymes potentially involved in the activation of the compounds. This study extends views about the antimicrobial and antifungal activities of the quinoxaline 1,4-dioxides and can potentially lead to the discovery of new antibacterial drugs.